School Management in Managing Inclusive Education at Buduran 2 and 6 Junior High School Sidoarjo, Indonesia - Lilik Sulistyowati; Dewie Tri Wijayanti Wardoyo; Karwanto Karwanto (International Journal of Emerging Research and Review, 2026)
Objective: This study aims to describe and analyze school management in inclusive education management through a multi-site study at Buduran 2 and 6 Junior High School Sidoarjo. Inclusive education provides opportunities for all students, including Students with Disabilities, to obtain quality educational services without discrimination. Method:  This research employed a qualitative approach with a multi-site study design. Data were collected through observation, in-depth interviews, and documentation studies involving principals, teachers, education staff, and parents. Data analysis was conducted using the Miles, Huberman, and Saldana model, which includes data condensation, data presentation, and conclusion drawing.  Results: The research results show that school management in inclusive education is implemented through planning, organizing, implementing, and evaluating. This includes internalizing an inclusive vision, establishing an inclusive team, developing an adaptive curriculum, implementing differentiated learning, and providing accessible facilities. Novelty: The novelty of this research lies in the disclosure of inclusive school management practices through a multi-site study approach which shows that the professional leadership of the principal plays an important role in integrating school management functions with inclusive values ​​to create an educational environment that is adaptive, tolerant, and supports student diversity.